Perception of Patient Safety in Health Care Professionals of a Teaching Hospital - Shadab, Wajiha; Afzal, Sadaf; Sultana, Saadia; Arif, Nighat; Khan, Muhammad Nadim Akbar; Tabassum, Hina (Pakistan Armed Forces Medical Journal, 2025)
Objective: To assess patient safety awareness among healthcare professionals in a tertiary care hospital. Study Design: Cross-sectional study Place and Duration of Study: Pakistan Railway Hospital, Rawalpindi, Pakistan from December 2023 to February 2024 Methodology: One hundred and fifty staff members were enrolled in the study after taking informed verbal consent. Demographic data and the closed-ended standard version of the Hospital Survey on Patient Safety Culture (HSOPSC) questionnaire were used for data collection. Results: Patient safety standards and perceptions were highly rated in terms of overall perceptions of patient safety, which ranged from good to acceptable. There was a positive response rate of 50.00%. Effective teamwork was demonstrated by 82.13% of hospital departments and units. Only 3-5 adverse events and 13.16% of clinician errors were reported in the previous 12 months. Honest sharing of information concerning mistakes and patient safety was claimed by 50.00% of respondents. Conclusion: Although patient safety standards and perceptions were highly rated in hospital departments, there is still room for improvement with regard to event reporting.